2012
DOI: 10.4161/cc.20121
|View full text |Cite
|
Sign up to set email alerts
|

Activation of multiple cancer pathways and tumor maintenance function of the 3q amplified oncogeneFNDC3B

Abstract: FNDC3B was recently identified in an oncogenomic screen for amplified oncogenes in hepatocellular carcinoma. It is located at 3q26 and is amplified in over 20% of cancers, usually as part of a broad amplified region encompassing the entire 3q arm. Consistent with an oncogenic role in multiple cancer types, we show here that overexpression of FNDC3B is capable of malignantly transforming mammary and kidney epithelial cells in addition to hepatocytes. To explore how FNDC3B transforms cells, we determined the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 39 publications
(42 reference statements)
9
64
0
1
Order By: Relevance
“…FNDC3B is mammary stem cell and cancer cell marker reported by many investigators. [23][24][25][26][27][28] Our earlier report of increased expression of FNDC3B in buffalo mammary cancer 24 was consistent with the present finding of goat mammary cancer. Cyclin B1 (CCNB1) is a cell cycle protein in G2/M transition.…”
supporting
confidence: 81%
“…FNDC3B is mammary stem cell and cancer cell marker reported by many investigators. [23][24][25][26][27][28] Our earlier report of increased expression of FNDC3B in buffalo mammary cancer 24 was consistent with the present finding of goat mammary cancer. Cyclin B1 (CCNB1) is a cell cycle protein in G2/M transition.…”
supporting
confidence: 81%
“…Cai et al . found that FNDC3B overexpression induces the epithelial-to-mesenchymal transition and activates several cancer pathways [33]. In addition, direct evidence from our knockdown and overexpression experiments indicates that FNDC3B promotes cell migration and tumor metastasis in HCC.…”
Section: Discussionmentioning
confidence: 71%
“…However, other evidence highlights FNDC3B as oncogene. First, FNDC3B is usually amplified [7, 33] and highly expressed in HCC and other cancers [7, 31, 3436]. Cai et al .…”
Section: Discussionmentioning
confidence: 99%
“…The function of FNDC3B in blood malignancies is unclear, although down-regulation of its expression is known to up-regulate miR-143 expression, which differentiates prostate cancer stem cells and promotes prostate cancer metastasis. 40,41 T-cell reactivity against mut-FNDC3B in patient 2 was polyfunctional (secreting IFN-g, granulocyte macrophage-colony-stimulating factor [GM-CSF], and IL-2), highly avid, and specific to the mut-FNDC3B peptide but not its wild-type counterpart ( Figure 5D). T-cell reactivity was abrogated by the presence of class I blocking antibody (W6/32), indicating that T-cell reactivity was class I restricted ( Figure 5E, left).…”
Section: 40mentioning
confidence: 99%